Implantação do modelo de gestão por processos em uma instituição de educação e tecnologia privada, sem fins lucrativos - Bôa Morte Costa, Eurídice (2016)
Each more time, the organizations are demanded for more agility in there deliveries, cheaper costs, more quality in the development of their products and to generate greater satisfaction to its customers. To achieve constant and sustainable results is fundamental to know and work in your business processes in a way that these processes delivery and support the organizational objectives established.In that way, is observed that in Brazil the number of organizations, from all sectors and sizes, which has been implementing the management for processes as a business strategy has grown. Considering the relevance of the theme, this study proposes to investigate the implementation of the management model by a business process in a private institution of professional education nonprofit.In that context, this paper analyzes questions related of the management of the professional education, the characteristic of the model implemented by the organization studied, motivations that led the organization to implement a management by processes and at what level the presence and effectiveness of the critical success factors supported the success and benefits of this deployment.To accomplish the expected results, it presents a bibliographical revision on the topic and then analyzed the information collected through interviews and questionnaires.Finally, this paper aims to explore one of the strategies used by world-class organizations, to gain a competitive advantage in increasingly complex markets on a non-profit institution with great market leadership.